Empowering Teacher Leadership: Mobilizing Education to Shape Perceptions - Devy Yulistiawati; Diding Nurdin; Eka Prihatin (STAI Hubbulwathan Duri, 2024)
The research explores teacher leadership development through mobilizing teacher education from the perspective of mobilizing teachers. It explores teacher responses to program implementation, teacher leadership development, constraints, management effectiveness, and sustainability. Research is explanatory research that combines quantitative survey methods and qualitative descriptive methods. The data collection involved 83 mobilizing teachers of Batch 7 in Purwakarta district. Research instruments are questionnaires, interview sheets, observations, and documentation. Data analysis was conducted in quantitative descriptive and qualitative triangulation. The results show that teacher education is an effective driver of developing teacher leadership through motivational support, teacher self-awareness, environmental support, and effective management. Obstacles faced include lack of internet facilities, school support, conflict of interest in teacher education mobilization with family and teaching work, finances, and teamwork. Time management is a complaint often in mobilizing teacher education that causes physical and mental health problems. Regardless of political issues and changes in the direction of education policy in the future, the survey results show that 100% of teachers voice the sustainability of teacher mobilization education. The research recommends the need for further analysis and research to consider that the program can be implemented with a lighter allocation of tasks and time but with a more optimal quality of achievement.